THE INFLUENCE OF RELIGIOSITY, BRAND IMAGE AND PERCEIVED VALUE ON BRAND LOYALTY IN SHARIA MINIMARKETS IN JABODETABEK - Ida Dayanti; Afif Zaerofi (Manis: Jurnal Manajemen dan Bisnis, 2026)
Sharia-based retail businesses, such as sharia minimarkets, have grown to meet the rising demand for halal products among Muslim consumers, yet brand loyalty in this sector remains underexplored. This study aims to examine the influence of religiosity, brand image, and perceived value on brand loyalty among 201 Muslim consumers in Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek). The study employs an explanatory quantitative method with Structural Equation Modeling–Partial Least Squares (SEM-PLS) analysis. The results indicate that religiosity, brand image, and perceived value each have a positive and significant effect on brand loyalty. Furthermore, religiosity significantly enhances both brand image and perceived value. The findings highlight the strategic importance of integrating religious values into branding and customer value creation to strengthen loyalty in the Islamic retail sector.